Coordinate systems used in geodesy. Geodetic orientation - Kasimov Mahmud (Open Academia, 2024)
This study investigates the evolution, precision, and challenges of geodetic coordinate systems such as WGS84 and NAD83. Emphasis is placed on their advancements in achieving sub-meter positional accuracy, alongside the persistent issues of datum discrepancies and horizontal shifts. The research underscores the critical role of transformation methodologies like NADCON and the potential of emerging satellite technologies to achieve sub-centimeter accuracy. These developments are essential for applications in urban planning, environmental monitoring, and navigation, emphasizing the need for global standardization of geodetic practices
Keywords: Geodetic coordinate systems; WGS84; NAD83